2019
DOI: 10.1177/1403494819852787
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of voluntary early retirement for older workers with and without chronic diseases: A Danish prospective study

Abstract: Aims: This study explored differences in determinants (i.e. health-related, work-related and social factors) of voluntary early retirement between older workers with and without chronic diseases in Denmark. Methods: Workers aged 56–64 years who were members of a voluntary early retirement scheme were selected from the Danish National Working Environment Survey (2008–2009) and were followed in a public register for four years. Cox regression analyses were performed separately for older workers with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Job dissatisfaction was a dominant risk factor for HRJL among both men and women independent of socio-demographic and lifestyle factors, findings consistent with those from European studies which have shown similar associations between job dissatisfaction [32][33][34] and other poor psychosocial work characteristics (effort-reward imbalance and low job control) [16,24,28,[33][34][35][36][37][38] and exit from work through disability retirement, receipt of disability benefits, or voluntary early retirement. Job satisfaction is a complex multi-faceted phenomenon incorporating perceived aspects of the work and its rewards as compared with its disadvantages.…”
Section: Plos Onesupporting
confidence: 87%
See 3 more Smart Citations
“…Job dissatisfaction was a dominant risk factor for HRJL among both men and women independent of socio-demographic and lifestyle factors, findings consistent with those from European studies which have shown similar associations between job dissatisfaction [32][33][34] and other poor psychosocial work characteristics (effort-reward imbalance and low job control) [16,24,28,[33][34][35][36][37][38] and exit from work through disability retirement, receipt of disability benefits, or voluntary early retirement. Job satisfaction is a complex multi-faceted phenomenon incorporating perceived aspects of the work and its rewards as compared with its disadvantages.…”
Section: Plos Onesupporting
confidence: 87%
“…Not coping with the physical demands of one's work was an important risk factor for HRJL in our final models for both men and women, robust to adjustment for all other factors and attenuating the association with difficulty managing financially. Other researchers have reported similar results in studies of exit from work through disability retirement, receipt of disability benefits, or voluntary early retirement [13,18,24,[31][32][33][34]. It seems that physically-demanding work (more common among people from more deprived backgrounds) becomes more difficult at older ages and that individuals who perceive a mismatch between what their work requires of them and their physical capacity are more likely to experience HRJL.…”
Section: Plos Onementioning
confidence: 62%
See 2 more Smart Citations
“…construction, manufacturing, service and eldercare) have a greater need for initiatives to reduce the aerobic workload-such as offering tailored exercise at the workplace for sustaining and improving cardiorespiratory fitness (Korshøj et al 2016;Hallman et al 2017;Lidegaard et al 2018;Lund Rasmussen et al 2018). Apart from increasing fitness, tailoring of manual work tasks to the cardiorespiratory fitness of workers may also be a solution for reducing the relative aerobic workload of individual workers-promoting balance between the capacity of workers and their tasks (which, currently, does not seem to be occurring Merkus et al 2019;Oakman et al 2019). Such tailoring would likely focus on equitable distribution in how work tasks are allocated (i.e., relative to capacity), but could also include other work modifications such as increased opportunity for rest breaks, shorter time at work, fewer days at work and help from fitter colleagues.…”
Section: Discussionmentioning
confidence: 99%